Laguna consumers’ buying tendencies towards HMO - Santos, Joseph Emil N. (Animo Repository, 2019)
Access to quality healthcare have been one of the major thrust in the country today. The government incessantly seeks solutions on how to improve the healthcare systems in the country and achieve universal healthcare for all. One of the areas that are being carried out by this objective is how to provide Filipinos better assistance with regard to their health financial needs.PhilHealth is a tax-exempted Government Corporation that was established to provide health insurance coverage to citizens of the Philippines. It has established program that would help minimize or subsidize medical costs. However, due to several factors, assistance given by PhilHealth is not enough to solve most of healthcare issues in the country.Private companies such as the Health Maintenance Organizations was also established to provide healthcare insurance to the society, it started to cater to employers who are seeking medical coverage benefits for their employees and its dependent, but due to the changes in the market, it began to develop and offer healthcare programs to informal sectors or consumers as well. Access to these different healthcare programs benefits mostly those living in Metro Manila and other key cities of the Philippines. However, the rural area, where most of the poor segment lives is still unexplored. With the help of these various HMO products offering, healthcare can be an accessible need in the country.Therefore, this study sought to identify the readiness of HMO products and services of those living outside Metro Manila using the Cue Utilization Theory. With an aim to determine and understand customer behaviour towards a complex product, three cues were initially narrowed down based from existing research in terms of what customer prioritize when a complex product is presented. Data were obtained via physical surveys from 250 respondents from the area of Laguna. One Way ANOVA was applied in order to test if all 3 cues should be part of a marketing communications plan. From the survey questionnaire, there were 4 questions presented per cue. Getting the mean average of each question, corresponding line item it identified consumer’s willingness to buy towards an HMO’s products and services. Results confirmed that Price and Product Benefits are important cues based on the respondents or prospective customers of an HMO. Because the two cues mean difference has no significant difference in the one way ANOVA performed for this study, research recommends that Price and Product Benefit should be the main focus in developing new products and what should be amplified in creating an effective marketing communication strategy for an HMO product. However, it is also recommended to further study different moderating variable in order to segment the target market efficiently and create a much more effective Marketing communications plan. HMO companies may create a marketing campaign that would emphasize the value of having an HMO product in the lives of the consumers while communicating as well the affordability it offers as compare to paying hospital bills using out-of-pocket budget.